2009
DOI: 10.1037/a0014965
|View full text |Cite
|
Sign up to set email alerts
|

When is straightforwardness a liability in negotiations? The role of integrative potential and structural power.

Abstract: Negotiations present individuals with a paradox. On the one hand, individuals are expected via social norms and formal regulations to be honest and straightforward in their negotiations. On the other hand, individuals who mislead their negotiation counterpart are often rewarded with more favorable settlements. The authors investigate this paradox by examining the relationship between negotiators' dispositional straightforwardness and concessions made during a negotiation. Drawing from the dual concern model (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 73 publications
2
41
0
Order By: Relevance
“…These results contribute to recent work in negotiation pointing to the importance at the bargaining table of both individual differences (e.g., Amanatullah et al., ; Barry & Friedman, ; DeRue et al., ; Dimotakis et al., ; Elfenbein, ; Judge et al., ) and orientations toward relationships (Curhan et al., ; Gelfand et al., ). On a broader level, negotiations can be viewed as a forum in which schemas about relationships play out, which may explain the influence of individual differences.…”
Section: Discussionsupporting
confidence: 74%
“…These results contribute to recent work in negotiation pointing to the importance at the bargaining table of both individual differences (e.g., Amanatullah et al., ; Barry & Friedman, ; DeRue et al., ; Dimotakis et al., ; Elfenbein, ; Judge et al., ) and orientations toward relationships (Curhan et al., ; Gelfand et al., ). On a broader level, negotiations can be viewed as a forum in which schemas about relationships play out, which may explain the influence of individual differences.…”
Section: Discussionsupporting
confidence: 74%
“…Just as too little trust can bring the negotiation to a stalemate, too much trust can lead to too much disclosure to the other. In at least one recent study, researchers demonstrated that excessive straightforwardness (candor) and trust can lead a negotiator to be too concerned with the other's interests, which can result in greater concession-making toward the other and perhaps poorer outcomes for oneself (DeRue et al, 2009). Similar research showed that high trust can make members of a work team reluctant to monitor one another's behavior in task performance.…”
Section: Question 3: What Is the Trust/honesty Dilemma In Negotiation?mentioning
confidence: 99%
“…Specifically, we found that agreeable negotiators achieved worse economic outcomes when negotiating with exploitative partners, but they achieved better economic outcomes when negotiating with non‐exploitative partners. Thus, it appears that agreeableness for a negotiator can be either an asset or liability in mixed negotiations, depending on the personality of the counterpart (see also, DeRue, Conlon, Moon, & Willaby, ; Wilson et al, ).…”
Section: Discussionmentioning
confidence: 99%